High Levels of Circulating Monocytic Myeloid-Derived Suppressive-Like Cells Are Associated With the Primary Resistance to Immune Checkpoint Inhibitors in Advanced Non-Small Cell Lung Cancer: An Exploratory Analysis - Bronte, Giuseppe; Petracci, Elisabetta; De Matteis, Serena; Canale, Matteo; Zampiva, Ilaria; Priano, Ilaria; Cravero, Paola; Andrikou, Kalliopi; Burgio, Marco Angelo; Ulivi, Paola; Delmonte, Angelo; Crinò, Lucio (Frontiers in Immunology, 2022)
Background Immunotherapy has become the standard of care for non-small cell lung cancer (NSCLC) patients. Some patients experience primary resistance to immunotherapy. Currently, we lack a marker of resistance to immunotherapy. Myeloid-derived suppressive-like cells (MDSCs) can reduce tumor response rate and survival outcomes. Methods This is an exploratory prospective observational study on metastatic NSCLC patients starting immunotherapy. Baseline peripheral blood samples were collected. Monocytic (M)-MDSCs were analyzed by flow cytometry. The main clinical outcomes were tumor response, progression-free survival (PFS), and overall survival (OS). The association between MDSC levels and tumor response was assessed. The association of PFS with OS was investigated using the Kaplan–Meier method and the Cox proportional hazards model. Results Twenty-two patients were included. The median M-MDSC value was higher in patients with progressive disease than patients with stable disease or partial response, p = 0.045. The median MDSC value in the overall population was 1.9. We found worse PFS (HR = 2.51; p = 0.046) and OS (HR = 2.68; p = 0.042) in patients with M-MDSC values higher than the median. Conclusions In this exploratory analysis, high M-MDSC levels are strongly associated with primary resistance to immunotherapy. If validated in larger studies, MDSC levels in blood samples could help to select NSCLC patients for higher benefit from immunotherapy.